2011
DOI: 10.1002/mds.23571
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic movement disorders: Past developments, current status, and future directions

Abstract: As the field of movement disorders has developed and matured over the past 25 years, psychogenic movement disorders have become increasingly recognized in subspecialty clinics. The diagnosis can be challenging and should be based on positive features rather than a purely exclusionary approach. The clinical phenotype can be quite varied, although certain categories of abnormal movement are more common than others. Electrophysiological studies may be particularly useful in establishing the diagnosis, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 78 publications
(98 reference statements)
2
35
1
Order By: Relevance
“…A functional gait disorder was at least probable in 16% of NOH patients. 20, 21 Finally, the use of medications overall known to potentially cause myoclonus was similar between the OM and NOH cohorts. A full list of the medications taken by the patients in this study can be found in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 90%
“…A functional gait disorder was at least probable in 16% of NOH patients. 20, 21 Finally, the use of medications overall known to potentially cause myoclonus was similar between the OM and NOH cohorts. A full list of the medications taken by the patients in this study can be found in Supplementary Table 2.…”
Section: Resultsmentioning
confidence: 90%
“…Because only a small group of patients develop dystonia in the setting of CRPS, some genetic predisposition might exist in patients who do develop this form of peripherally induced dystonia. 140 The presence of affective disorders and of psychogenic features in these patients has led some researchers to propose that dystonia in the setting of peripheral injury is largely of psychogenic origin 137,143 or a form of body integrity identity disorder. 144 More data are needed to better understand the CRPS dystonia syndrome.…”
Section: Peripherally Induced Dystonia and Complex Regional Painmentioning
confidence: 99%
“…Its diagnosis is based on a sudden onset, irregular and inconsistent oscillatory movements with distractibility and suggestibility. Entrainment, defined as changing frequency of psychogenic tremor in adaption to voluntary tasks with determined frequency and performed with controlateral arm such as tapping in time to a metronome, can be very helpful in differentiation from ET 41. Multiple somatization signs, previous psychiatric diagnoses, and possible secondary gain can be also helpful for the diagnosis of psychogenic tremor 42…”
Section: Essential Tremor: Diagnosis and Differential Diagnosismentioning
confidence: 99%